An ALMA Study of the Massive Molecular Clump N159W-North in the Large Magellanic Cloud: A Possible Gas Flow Penetrating One of the Most Massive Protocluster Systems in the Local Group - Tokuda, Kazuki; Minami, Taisei; Fukui, Yasuo; Inoue, Tsuyoshi; Nishioka, Takeru; Tsuge, Kisetsu; Zahorecz, Sarolta; Sano, Hidetoshi; Konishi, Ayu; Chen, C-H Rosie; Sewilo, Marta; Madden, Suzanne C.; et al. (Astrophysical Journal, 2022)
Massive dense clumps in the Large Magellanic Cloud can be an important laboratory to explore the formation of populous clusters. We report multiscale ALMA observations of the N159W-North clump, which is the most CO-intense region in the galaxy. High-resolution CO isotope and 1.3 mm continuum observations with an angular resolution of similar to 0.'' 25 (similar to 0.07 pc) revealed more than five protostellar sources with CO outflows within the main ridge clump. One of the thermal continuum sources, MMS-2, shows an especially massive/dense nature whose total H-2 mass and peak column density are similar to 10(4) M (circle dot) and similar to 10(24) cm(-2), respectively, and harbors massive (similar to 100 M (circle dot)) starless core candidates identified as its internal substructures. The main ridge containing this source can be categorized as one of the most massive protocluster systems in the Local Group. The CO high-resolution observations found several distinct filamentary clouds extending southward from the star-forming spots. The CO (1-0) data set with a larger field of view reveals a conical, similar to 30 pc long complex extending toward the northern direction. These features indicate that a large-scale gas compression event may have produced the massive star-forming complex. Based on the striking similarity between the N159W-North complex and the other two previously reported high-mass star-forming clouds in the nearby regions, we propose a "teardrops inflow model" that explains the synchronized, extreme star formation across >50 pc, including one of the most massive protocluster clumps in the Local Group.
CRIS-Team WoS Importer:2022-07-08

An Unbiased CO Survey Toward the Northern Region of the Small Magellanic Cloud with the Atacama Compact Array. II. CO Cloud Catalog - Ohno, Takahiro; Tokuda, Kazuki; Konishi, Ayu; Matsumoto, Takeru; Sewiło, Marta; Kondo, Hiroshi; Sano, Hidetoshi; Tsuge, Kisetsu; Zahorecz, Sarolta; Goto, Nao; Neelamkodan, Naslim; Wong, Tony; et al. (Astrophysical Journal, 2023)
The nature of molecular clouds and their statistical behavior in subsolar metallicity environments are not fully explored yet. We analyzed data from an unbiased CO (J = 2-1) survey at the spatial resolution of ∼2 pc in the northern region of the Small Magellanic Cloud with the Atacama Compact Array to characterize the CO cloud properties. A cloud-decomposition analysis identified 426 spatially/velocity-independent CO clouds and their substructures. Based on the cross-matching with known infrared catalogs by Spitzer and Herschel, more than 90% CO clouds show spatial correlations with point sources. We investigated the basic properties of the CO clouds and found that the radius-velocity linewidth (R-σ v ) relation follows the Milky Way-like power-law exponent, but the intercept is ∼1.5 times lower than that in the Milky Way. The mass functions (dN/dM) of the CO luminosity and virial mass are characterized by an exponent of ∼1.7, which is consistent with previously reported values in the Large Magellanic Cloud and in the Milky Way.
CRIS-Team Scopus Importer:2023-06-30

eROSITA studies of the Carina nebula - Sasaki, Manami; Robrade, Jan; Krause, Martin G.H.; Knies, Jonathan; Tsuge, Kisetsu; Pühlhofer, Gerd; Strong, Andrew (Astronomy & Astrophysics, 2024)
Context. During the first four all-sky surveys eRASS:4, which was carried out from December 2019 to 2021, the extended Roentgen Survey with an Imaging Telescope Array (eROSITA) on board the Spektrum-Roentgen-Gamma (Spektr-RG, SRG) observed the Galactic H II region, the Carina nebula. Aims. We analysed the eRASS:4 data to study the distribution and spectral properties of the hot interstellar plasma and the bright stellar sources in the Carina nebula. Methods. The spectral extraction regions of the diffuse emission were defined based on the X-ray spectral morphology and multi-wavelength data. The spectra were fit with a combination of thermal and non-thermal emission models. The X-ray bright point sources in the Carina nebula are the colliding wind binary η Car, several O stars, and Wolf-Rayet (WR) stars. We extracted the spectra of the brightest stellar sources, which can be well fit with a multi-component thermal plasma model. Results. The spectra of the diffuse emission in the brighter parts of the Carina nebula are well reproduced by two thermal models, a lower-temperature component (∼0.2 keV) and a higher-temperature component (0.6-0.8 keV). An additional non-thermal component dominates the emission above ∼1 keV in the Central region around η Car and the other massive stars. Significant orbital variation in the X-ray flux was measured for η Car, WR 22, and WR 25. η Car requires an additional time-variable thermal component in the spectral model, which is associated with the wind-wind collision zone. Conclusions. Properties such as temperature, pressure, and luminosity of the X-ray emitting plasma in the Carina nebula derived from the eROSITA data are consistent with theoretical calculations of emission from superbubbles. This confirms that the X-ray emission is caused by the hot plasma inside the Carina nebula that has been shocked-heated by the stellar winds of the massive stars, in particular, of η Car.
CRIS-Team Scopus Importer:2025-02-04
Keywords: HII regions; ISM: bubbles; ISM: structure; stars: massive; X-rays: ISM; X-rays: stars

Exploring the evolution of giant molecular clouds in one of the nearest spiral galaxies M33 - Konishi, Ayu; Muraoka, Kazuyuki; Tokuda, Kazuki; Fujita, Shinji; Yamada, Rin I.; Demachi, Fumika; Tachihara, Kengo; Fukui, Yasuo; Kobayashi, Masato I.N.; Tsuge, Kisetsu; Kawamura, Akiko; Onishi, Toshikazu (Resolving the Rise and Fall of Star Formation in Galaxies, 2021)
The evolution of giant molecular clouds (GMCs), which are the main sites of star formation, is essential for unraveling how stars form and how galaxies evolve. We analyzed the M33 CO(J = 2–1) data with spatial resolution of 39 pc obtained by ALMA-ACA 7 m array combined with IRAM 30 m. We identified 736 GMCs and classified them into three types; Type I: associated with no H ii regions, Type II: associated with H ii regions with the Hα luminosity L(Hα) < 1037.5erg s−1, Type III: associated with H ii regions with L(Hα) > 1037.5erg s−1. We found that mass, size, and velocity dispersion of GMCs slightly increase in the order of Type I, II, and III GMCs. Type III GMCs mainly exist in the spiral arm, while many of Type I and Type II GMCs are distributed in the inter-arm. Assuming that the star formation proceeds steadily, we roughly estimated the total GMC lifetime of 30 Myr.
CRIS-Team Scopus Importer:2024-12-16
Keywords: galaxies: Local Group; galaxies: spiral; ISM: molecules; stars: formation

Massive star formation in the Carina nebula complex and Gum 31. II. A cloud–cloud collision in Gum 31 - Fujita, Shinji; Sano, Hidetoshi; Enokiya, Rei; Hayashi, Katsuhiro; Kohno, Mikito; Tsuge, Kisetsu; Tachihara, Kengo; Nishimura, Atsushi; Ohama, Akio; Yamane, Yumiko; Ohno, Takahiro; Yamada, Rin; et al. (Publications of the Astronomical Society of Japan, 2021)
We present the results of analyses of the 12CO (J = 1–0), 13CO (J = 1–0), and 12CO (J = 2–1) emission data toward Gum 31. Three molecular clouds separated in velocity were detected at -25, -20, and -10 km s-1. The velocity structure of the molecular clouds in Gum 31 cannot be interpreted as an expanding motion. Two of them, the -25 km s-1 cloud and the -20 km s-1 cloud, are likely to be associated with Gum 31, because their 12CO (J = 2–1)/12CO (J = 1–0) intensity ratios are high. We found that these two clouds show the observational signatures of cloud–cloud collisions (CCCs): a complementary spatial distribution and a V-shaped structure (bridge features) in the position–velocity diagram. In addition, their morphology and velocity structures are very similar to the numerical simulations conducted by the previous studies. We propose a scenario that the -25 km s-1 cloud and the -20 km s-1 cloud collided and triggered the formation of the massive star system HD 92206 in Gum 31. This scenario can explain the offset of the stars from the center and the morphology of Gum 31 simultaneously. The timescale of the collision was estimated to be ∼1 Myr by using the ratio between the path length of the collision and the assumed velocity separation. This is consistent with that of the CCCs in the Carina Nebula Complex in our previous study.
CRIS-Team Scopus Importer:2021-10-29
Keywords: ISM: clouds; ISM: individual (Carina); Radio lines: ISM

Multiwavelength study of the H II region LHA 120-N11 in the Large Magellanic Cloud with eROSITA - Tsuge, Kisetsu; Sasaki, Manami; Knies, Jonathan; Haberl, F.; Points, S.; Maitra, C.; Filipovic, M. D.; Staveley-Smith, L.; Koribalski, B. S.; Kerp, J. (Astronomy & Astrophysics, 2024)
Aims. We studied the diffuse X-ray emission around the HII region LHA 120-N11, which is one of the most active star-forming regions in the Large Magellanic Cloud. We want to determine the nature of the diffuse X-ray emission and improve our understanding of its origin including related interactions with the cold interstellar medium. Methods. We analyzed the diffuse X-ray emission observed with the extended Roentgen Survey with an Imaging Telescope Array (eROSITA) on the Spectrum-Roentgen-Gamma mission to determine the physical properties of the hot diffuse X-ray emission. Four spectral extraction regions were defined based on the morphology of the X-ray emission. We also studied HI and CO data, as well as Hα line emission in the optical, and compared them with the properties of the diffuse X-ray emission. Results. The X-ray emission in the four regions is well fitted with an absorbed model consisting of thermal plasma models (vapec) yielding temperatures of kT = 0.2 keV and kT = 0.8 1.0 keV. The comparison of the X-ray absorption column density and the hydrogen column density shows that the X-ray dark lane located north of N11 is apparently caused by the absorption by HI and CO clouds. By estimating the energy budget of the thermal plasma, we also investigated the heating mechanism of the X-ray emitting plasma. The energy of the diffuse X-ray emission in the superbubble which is a star-forming bubble with a radius of 120 pc including OB associations LH9, LH10, LH11, and LH13 can be explained by heating from high-mass stars. In the surrounding regions we find that the energy implied by the X-ray emission suggests that additional heating might have been caused by shocks generated by cloud cloud collisions.
CRIS-Team Scopus Importer:2024-07-05
Keywords: Magellanic Clouds; X-rays: ISM

Three-dimensional geometry and dust/gas ratios in massive star-forming regions over the entire LMC as revealed by the IRSF/SIRIUS survey - Furuta, Takuya; Kaneda, Hidehiro; Kokusho, Takuma; Nakajima, Yasushi; Fukui, Yasuo; Tsuge, Kisetsu (Publications of the Astronomical Society of Japan, 2022)
We derive the entire dust extinction (A(V)) map for the Large Magellanic Cloud (LMC) estimated from the color excess at near-infrared wavelengths. Using the percentile method we recently adopted to evaluate A(V) distribution along the line of sight, we derive three-dimensional (3D) A(V) maps of the three massive star-forming regions of N44, N79, and N11 based on the IRSF/SIRIUS point source catalog. The 3D A(V) maps are compared with the hydrogen column densities N(H) of three different velocity components where one is of the LMC disk velocity and the other two are of velocities lower than the disk velocity. As a result, we obtain a 3D dust geometry suggesting that gas collision is ongoing between the different velocity components. We also find differences in the timing of the gas collision between the massive star-forming regions, which indicates that the gas collision in N44, N79, and N11 occurred later than that in 30 Doradus. In addition, a difference of a factor of two in A(V)/N(H) is found between the velocity components for N44, while a significant difference is not found for N79 and N11. From the 3D geometry and A(V)/N(H) in each star-forming region, we suggest that the massive star formation in N44 was induced by an external trigger of tidal interaction between the LMC and the Small Magellanic Cloud, while that in N79 and N11 is likely to have been induced by internal triggers such as gas converging from the galactic spiral arm and expansion of a supershell, although the possibility of tidal interaction cannot be ruled out.
CRIS-Team WoS Importer:2022-06-03